Thrombophilic Genotypes in Subjects with Idiopathic Antiphospholipid Antibodies – Prevalence and Significance - Ames, Paul R. J.; Tommasino, Catello; D’Andrea, Giovanna; Iannaccone, Luigi; Brancaccio, Vincenzo; Margaglione, Maurizio (Thrombosis and Haemostasis, 1998)
To evaluate the significance of common thrombophilic genotypes in subjects with idiopathic antiphospholipid antibodies (aPL) we determined the methylenetetrahydrofolate reductase C677→ (MTHFR) and factor V A506→ G (FV Leiden) polymorphisms in 49 subjects with idiopathic aPL (57% of whom suffered spontaneous vein thrombosis), in 70 subjects with a history of spontaneous vein thrombosis and in 193 healthy subjects. The prevalence of MTHFR C677→+/+ (homozygotes) was 25%, 18% and 17% respectively amongst aPL thrombotics, non aPL thrombotics and controls and that of MTHFR C677→+/– (heterozygotes) was 53%, 59% and 53% respectively in the same groups. The prevalence of FV Leiden was higher in aPL thrombotics (14%) and in non aPL thrombotics (18%) than in controls (4%) (p ≤ = 0.05). APL thrombotics with MTHFR C677→+/+ had a lower mean age at first thrombotic event (22 ± 6 years) than aPL thrombotics with MTHFR C677→+/– and non mutated considered together (38 ± 14 years, p = 0.0004) and than non aPL thrombotics with MTHFR C677→+/+ (38 ± 14 years, p = 0.003). FV Leiden may con tribute to the hypercoagulability of a small, albeit significant proportion of thrombotic aPL subjects, whereas the association between MTHFR C677→+/+ and aPL may have an impact on age at first occlusive event and suggests a possible pathogenetic interaction.